2016
DOI: 10.1002/chem.201601173
|View full text |Cite
|
Sign up to set email alerts
|

Light‐ and Solvent‐Controlled Self‐Assembly Behavior of Spiropyran–Polyoxometalate–Alkyl Hybrid Molecules

Abstract: A molecular photochromic spiropyran-polyoxometalate-alkyl organic-inorganic hybrid has been synthesized and fully characterized. The reversible switching of the hydrophobic spiropyran fragment to the hydrophilic merocyanine one can be easily achieved under light irradiation at different wavelengths. This switch changes the amphiphilic feature of the hybrid, leading to a light-controlled self-assembly behavior in solution. It has been shown that the hybrid can reversibly self-assemble into vesicles in polar sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Very interestingly, R g / R h is close to 1 ( R h =95.6 nm, R g =97.8 nm). According to literatures, this ratio indicates that the self‐assembly of POM‐TANI@EB should be a typical spherical vesicle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very interestingly, R g / R h is close to 1 ( R h =95.6 nm, R g =97.8 nm). According to literatures, this ratio indicates that the self‐assembly of POM‐TANI@EB should be a typical spherical vesicle.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Inspired by nature,l ots of self-assembled systemsi nl iving organisms adaptt hemselves to changes of environments through responding to externalp hysical and chemicals timuli. [7] To mimic the art of nature, many of POMbased self-assembled systems are elegantly devised and endowed with fascinating stimuli-responsiveness to pH, [8] metal ions, [9] or UV radiation, [10] .T ot he best of our knowledge,t here remains great opportunities to construct POM-based self-assembled systemswith redox-responsive characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy could be used to precisely fine‐tune the sizes of NP aggregates, as shown in Figure e. Interestingly, other studies have demonstrated that once assembled, MC‐functionalized NPs remain stable even under prolonged exposure to visible light, which highlights the strength of the MC–MC interactions.…”
Section: Nanoparticles Surface‐functionalized With Photoswitchable Momentioning
confidence: 95%
“…In }], by covalently grafting a photoswitchable spiropyran (SP) fragment and a long hydrophobic alkyl chain. 141 Under UV irradiation (l = 365 nm) colourless and hydrophobic SP underwent a C-O bond cleavage resulting in the formation of a zwitterionic merocyanine (MC) isomer, which is hydrophilic and strongly absorbs in the visible regions. This conversion triggered the self-assembly processes in mixed solvents (Fig.…”
Section: Mixed-addenda Wells-dawsonmentioning
confidence: 99%